(untitled) (International Journal of Engineering and Computer Science, 2015)
In the digital world, digital media is having a great impact and protection on such digital content is becoming necessary nowadays. Various image file formats are available for digital media. The digital content is often encrypted for security purpose. The encryption will change the content into unreadable format. Then the digital content can also be watermarked for tamper detection or for copyright protection. Encryption is often used but once it is decrypted it is not protected. So watermark is another level of security for digital content. Watermark remains also after decryption to identify owner of the digital content. This paper provides a survey on various ways to provide copyright protection for media content